Potential Of Probiotics and Natural Ingredients As Antibiofilm And Antibacterial : A Systematic Review - Kadek Dwi Adi Mas Putrayana; Ida Bagus Nyoman Putra Dwija; Komang Vindya Triananda; I Gusti Ayu Nastiti Wahyu Handayani; Luh Putu Rinawati; Ni Putu Kusuma Santhi Y (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Biofilms are surface-adhering communities of microorganisms that produce extracellular polymeric substances (EPS) and can grow on any surface, including metal, plastic, glass, soil particles, stainless steel, wood, and biotic surface. biofilm infections lead to different disorders, for instance, diabetes mellitus, dental caries, medical implants and wound infections that significantly affect the quality of life, cancer development, and subsequently, increase the global morbidity rate.This study aims to summarize the recent evidence supporting the potentional of probiotic and natural ingridient as antibiofilm and antibacterial using a PRISMA-oriented (Preferred Reporting Items for Systematic reviews and Meta-analyses) statement. This review found significant aspects exemplified by the properties of probiotics and natural ingridients related to as antibiofilm and antibacterial for further indepth studies to make it into pilot scales.